A descriptive study to assess the knowledge level healthcare providers regarding the role of artificial intelligence in patient care in selected primary health care centres (International Journal of Food and Nutritional Sciences, 2025)
Artificial Intelligence (AI) is transforming healthcare by improving diagnostic accuracy, streamlining patient care, and enhancing clinical decision-making. However, the knowledge level of healthcare providers regarding AI's role in patient care remains underexplored, particularly in primary healthcare settings.